2014
DOI: 10.1093/jis/14.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of reference genes for functional studies in the Calliphoridae family

Abstract: The genera Cochliomyia and Chrysomya contain both obligate and saprophagous flies, which allows the comparison of different feeding habits between closely related species. Among the different strategies for comparing these habits is the use of qPCR to investigate the expression levels of candidate genes involved in feeding behavior. To ensure an accurate measure of the levels of gene expression, it is necessary to normalize the amount of the target gene with the amount of a reference gene having a stable expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…RPL32 should be avoided when evaluating gene expression in samples from pupal tissue; RPS17 in male and blood fed female adult tissue; and GAPDH in samples derived from non-blood fed female adults as well as Aag2 cells. The frequency with which GAPDH appeared at the lower end of consensus rankings was surprisingly high, as the reliability of the gene as a reference in arthropods has been shown time and time again 43 44 45 . Nevertheless, given the high standard deviation and overall instability of gene as displayed by our data, we are comfortable in suggesting caution when utilizing GAPDH in regards to Ae.…”
Section: Discussionmentioning
confidence: 99%
“…RPL32 should be avoided when evaluating gene expression in samples from pupal tissue; RPS17 in male and blood fed female adult tissue; and GAPDH in samples derived from non-blood fed female adults as well as Aag2 cells. The frequency with which GAPDH appeared at the lower end of consensus rankings was surprisingly high, as the reliability of the gene as a reference in arthropods has been shown time and time again 43 44 45 . Nevertheless, given the high standard deviation and overall instability of gene as displayed by our data, we are comfortable in suggesting caution when utilizing GAPDH in regards to Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only a few studies were on the reference evaluation in blowfly species. Cardoso et al 2014 suggested that Actin, GAPDH, and Rpl49 were the most stable genes among life stages in three Calliphoridae species ( Cochliomyia hominivorax Coquerel, C. macellaria Fabricius, and C. albiceps Wiedemann) by designing primers with conserved regions of six candidate reference genes [ 34 ]. In the Australian sheep blowfly, Lucilia cuprina , 18S, 28SrRNA, GST1 (Glutathione-S-transferase), β-TUB and RPLPO (Acidic ribosomal phosphoprotein PO) were suggested to be an ideal set of genes for data normalization across all life stages, while GAPDH was proven to be a poor reference gene [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…MNE is the ratio of the mean of the reference and target genes cycle thresholds ( Ct s), including efficiency values: MNE = ( E reference ) Ctreference ∕( E target ) Cttarget . All mRNA levels were normalized using the mean of the reference genes Gapdh and Rp49 , both validated in a previous study (Cardoso et al, 2014). …”
Section: Methodsmentioning
confidence: 99%